Preparation method and application of bionic enzyme aerogel reactor

By preparing a bionic tanninase-pGSC/TiNFs enzyme reactor with honeycomb pore structure, the problem of insufficient enzyme stability was solved, efficient immobilization and biocatalytic transformation of enzymes were achieved, and the application potential of biomass transformation was demonstrated.

CN119307485AActive Publication Date: 2025-01-14ZHEJIANG FORESTRY UNIVERSITY

Patent Information

Application Number
CN202411845352.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Inadequate stability of enzymes, difficulty in denaturation and separation and reuse limits efforts to continue to convert reactants into products and reduce production costs.

Method used

Using the preparation method of a bionic enzyme aerogel reactor, titanium dioxide nanofibers were prepared by solvent heat treatment, frozen casting and vacuum drying, combined with glycidyl methacrylate and methacryloylethylsulfobetaine crosslinking agent to form a crosslinking agent with Bionic tannins-pGSC/TiNFs enzyme reactor with honeycomb pore structure and covalently immobilize tannins under mild conditions.

Benefits of technology

The pH value and thermal tolerance, thermal stability, storage stability and reusability of the enzyme are improved, and efficient biocatalytic conversion under continuous flow conditions is achieved, demonstrating the application potential of biomass conversion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307485A_ABST
    Figure CN119307485A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation methods of biomimetic enzyme reactors, and particularly discloses a preparation method and application of a biomimetic enzyme aerogel reactor, and the preparation method specifically comprises the following steps: step S1, firstly preparing titanium dioxide nanofibers (TiNFs) through solvent heat treatment; step S2, carrying out freeze casting and vacuum drying on an aqueous dispersion containing titanium dioxide nanofibers (TiNFs), chitosan methacrylate (CSMA) and a cross-linking agent to obtain a bionic C / TiNFs aerogel reactor with vertically arranged channels; step S3, carrying out polymerization and modification on glycidyl methacrylate (GMA), methacryloylethyl sulfobetaine (SBMA) and an N, N '-methylene bisacrylamide (MBA) cross-linking agent on a skeleton of the simulated gas gel reactor; and step S4, covalently immobilizing tannase in the bionic gas gel reactor under a mild condition, so as to obtain the bionic tannase-pGSC / TiNFs enzyme reactor. The bionic tannase-pGSC / TiNFs enzyme reactor disclosed by the invention is composed of TiNFs, CSMA (Carboxymethyl Methacrylate), polyglycidyl methacrylate (PGMA), polymethylacryloyl ethyl sulphobetaine (PSBMA) and immobilized tannase, has vertically arranged channels, and can be used as a tissue cell reactor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation methods of bionic enzyme reactors, in particular to a preparation method and application of a bionic enzyme aerogel reactor. Background Art

[0002] Enzymes have the characteristics of high specificity, good biocompatibility, and high catalytic activity, and are widely used in food production, biochemical testing, and pharmaceuticals. However, obstacles such as insufficient stability, enzyme denaturation, and difficulty in separation and reuse limit efforts to continuously convert reactants into products and reduce production costs. In this regard, enzyme immobilization technology is considered to be an effective way to overcome the above challenges. At present, a variety of enzyme immobilization methods have been developed, including physical adsorption, encapsulation, and chemical bonding. Although the stability of the enzyme after immobilization has been improved to a certain extent, it is still insufficient overall. Summary of the invention

[0003] In view of the technical problems mentioned in the background technology, the present invention provides a preparation method and application of a bionic enzyme aerogel reactor.

[0004] The technical solution adopted by the present invention is: a method for preparing a bionic enzyme aerogel reactor, which specifically comprises the following steps: Step S1, first preparing titanium dioxide nanofibers (TiNFs) by solvent thermal treatment; Step S2, freeze-casting and vacuum drying an aqueous dispersion containing titanium dioxide nanofibers (TiNFs), chitosan methacrylate (CSMA) and a cross-linking agent to obtain a biomimetic C / TiNFs aerogel reactor with vertically arranged channels; Step S3, polymerizing and modifying glycidyl methacrylate (GMA) monomer, methacryloylethyl sulfobetaine (SBMA) monomer and N,N'-methylenebisacrylamide (MBA) crosslinker on the skeleton of the biomimetic aerogel reactor; Step S4, covalently immobilizing tannase in a biomimetic aerogel reactor under mild conditions, thereby obtaining a biomimetic tannase-pGSC / TiNFs enzyme reactor.

[0005] The present invention is further configured such that the bionic tannase-pGSC / TiNFs enzyme reactor prepared in step S4 is cylindrical.

[0006] The present invention is further configured such that the bionic tannase-pGSC / TiNFs enzyme reactor prepared in step S4 exhibits a 3D hierarchical cell-like structure having honeycomb pores therein.

[0007] The present invention is further configured such that the size of the honeycomb holes is 20-100 μm, the mesh hole walls are composed of nanofibers and polymers, and have a thickness of 0.2-2 μm.

[0008] The present invention is further configured such that the biomimetic tannase-pGSC / TiNFs enzyme reactor also exhibits unidirectional, vertically arranged and interconnected channels in the longitudinal direction.

[0009] The present invention is further configured as an application of a bionic enzyme aerogel reactor, wherein the bionic tannase-pGSC / TiNFs enzyme reactor is applied to biocatalytic engineering.

[0010] The beneficial effects of the present invention are as follows: compared with the prior art, the bionic tannase-pGSC / TiNFs enzyme reactor of the present invention is composed of TiNFs, CSMA, PGMA, PSBMA and immobilized tannase, and has vertically arranged channels. Since the reactor has the characteristics of honeycomb structure, rapid mass transfer, comfortable microenvironment and PSBMA-modified substrate enrichment effect, compared with enzyme reactors without PSBMA and free tannase, the bionic tannase-pGSC / TiNFs enzyme reactor exhibits enhanced pH value and thermal tolerance, thermal stability, storage stability and reusability. The bionic tannase-pGSC / TiNFs enzyme reactor can act as a tissue cell reactor, which can continuously and effectively convert tannin into gallic acid and glucose under continuous flow conditions, demonstrating the application of biomass conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The present invention is a schematic diagram of a preparation method of a bionic tannase-pGSC / TiNFs enzyme reactor having vertically arranged channels and its application in continuous flow catalytic conversion of tannins.

[0012] Figure 2 (a) The bionic enzyme reactor of the present invention, (be) SEM photos of the lateral (bd) and vertical cross-sections (e), and (f) the water contact angle diagram of the bionic tannase-pGSC / TiNFs enzyme reactor.

[0013] Figure 3 (a) Zeta potential values ​​of different samples in water after grinding, (b) water flux of different samples under gravity without additional auxiliary pressure, (c) compressive stress-strain curves of different samples, and (d) tannase immobilization amount diagram in different reactors in the present invention.

[0014] Figure 4 Graph showing the effects of (a) immobilization time, (b) tannase concentration, (c) pH value and (d) reaction temperature on the enzyme immobilization amount and activity of the bionic tannase-pGSC / TiNFs enzyme reactor in the present invention.

[0015] Figure 5 Graph showing the effects of different conditions on the activities of immobilized and free tannases in the present invention; (a) pH value, (b) temperature, (c) storage time, and (d) multiple cycles.

[0016] Figure 6 Figure 2 shows the continuous flow catalytic conversion of tannin using the biomimetic tannase-pGSC / TiNFs enzyme reactor in the present invention; (a) photo of the test equipment, (b) conversion efficiency at different flow rates, (c) conversion efficiency after 10 cycles of 100 mL of solution per cycle, and (d) conversion efficiency after 15 days of continuous use. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] In order to solve the problems existing in the background technology, the present application proposes the following technical solution: a preparation method and application of a bionic enzyme aerogel reactor, which specifically includes the following steps: Manufacturing process such as Figure 1 As shown in a.

[0019] Step S1, first preparing titanium dioxide nanofibers (TiNFs) by solvent thermal treatment; Step S2, freeze-casting and vacuum drying an aqueous dispersion containing titanium dioxide nanofibers (TiNFs), chitosan methacrylate (CSMA) and a cross-linking agent to obtain a biomimetic C / TiNFs aerogel reactor with vertically arranged channels; Step S3, polymerizing and modifying glycidyl methacrylate (GMA) monomer, methacryloylethyl sulfobetaine (SBMA) monomer and N,N'-methylenebisacrylamide (MBA) crosslinker on the skeleton of the biomimetic aerogel reactor; Step S4, covalently immobilize tannase in the biomimetic aerogel reactor under mild conditions to obtain a biomimetic tannase-pGSC / TiNFs enzyme reactor (Tannase-pCSC / TiNFs). The biomimetic tannase-pGSC / TiNFs enzyme reactor has high porosity and water flux. When the solution flows through the reactor, the reactant tannin can be effectively converted into gallic acid and glucose (Figure 1b).

[0020] Among them, the bionic tannase-pGSC / TiNFs enzyme reactor prepared in step S4 is cylindrical, and the bionic tannase-pGSC / TiNFs enzyme reactor exhibits a 3D layered cell-like structure, and its structure has the characteristics of honeycomb pores. The size of the honeycomb pores is 20-100 μm, and the mesh pore walls are composed of nanofibers and polymers with a thickness of 0.2-2 μm. The bionic tannase-pGSC / TiNFs enzyme reactor also exhibits unidirectional, vertically arranged and interconnected channels in the longitudinal direction.

[0021] Further explanation is as follows: The preparation method of biomimetic CSMA / TiNFs (C / TiNFs) aerogel is as follows: 20.0 g of titanium dioxide nanofibers (TiNFs) (20 mg g –1 ) aqueous suspension, 10.0 g chitosan methacrylate (CSMA) (20 mg g –1 ) solution and 100 μL of polyethylene glycol diglycidyl ether were mixed and stirred for 20 min, and the mixture was added to a cylindrical mold, and then a directed freezing process was performed using liquid nitrogen. The frozen samples were freeze-dried and frozen at 60 o C for 4 h to obtain biomimetic C / TiNFs aerogel.

[0022] The synthesis method of the biomimetic tanninase-pGMA / SBMA / CSMA / TiNFs (Tannase-pGSCS / TiNFs) enzyme reactor is as follows: 400 mg of glycidyl methacrylate, 12 mg of K2S2O8, 2 mL of methacryloylethyl sulfobetaine and 12 mg of N,N'-methylenebisacrylamide were dissolved in 4 mL of deionized water. The resulting solution was added dropwise to the biomimetic C / TiNFs aerogel. The sample was heated at 80 o C for 1 h to obtain a biomimetic pGMA / SBMA / CSMA / TiNFs (pGSC / TiNFs) reactor. The sample was washed with deionized water to remove the residual chemicals. Subsequently, the pGSC / TiNFs reactor was added with a 0.5 mg mL –1 10 mL of tannase-containing phosphate buffer (pH 7.0). o C for 12 h, and the obtained tannase immobilized enzyme reactor (Tannase-pGSCS / TiNFs) was washed several times with phosphate buffer (pH 7.0) and stored in a refrigerator.

[0023] In addition, the determination method of enzyme activity, enzyme immobilization amount and conversion efficiency of the biomimetic tannase-pGSCS / TiNFs enzyme reactor in the continuous flow mode is as follows: The activity of tannase was studied by measuring the amount of gallic acid produced from methyl gallate. The amount of immobilized enzyme in the biomimetic tannase-pGSCS / TiNFs enzyme reactor was determined using the Bradford method. The continuous flow catalytic conversion test was performed in a conventional chromatographic column. A biomimetic tannase-pGSCS / TiNFs enzyme reactor with a diameter of 26 mm and a height of 26 mm was placed at the bottom of the column. A peristaltic pump was used to pump tannin (1 mg mL –1 ) was injected into the top surface of the biomimetic tannase-pGSCS / TiNFs enzyme reactor, and the initial solution and the filtered solution after catalytic treatment were collected and analyzed by UV-visible absorption spectroscopy.

[0024] In summary, the surface and internal morphology of the biomimetic tannase-pGSC / TiNFs enzyme reactor were observed. The biomimetic tannase-pGSC / TiNFs enzyme reactor was cylindrical and could be easily prepared in a cylindrical mold ( Figure 2 a); Figure 2 bd show scanning electron microscopy (SEM) images in the lateral direction, the biomimetic tannase-pGSC / TiNFs enzyme reactor exhibits a 3D hierarchical cell-like structure, which is similar to the honeycomb pores in natural trees; The honeycomb pores have a size of 20-100 μm, and the mesh pore walls are composed of nanofibers and polymers with a thickness of 0.2-2 μm. In addition, the biomimetic tannase-pGSC / TiNFs enzyme reactor exhibits unidirectional, vertically arranged and interconnected channels in the longitudinal direction ( Figure 2 e). This result is attributed to the continuous growth of ice crystals in the vertical direction; In addition, the biomimetic tannin enzyme-pGSC / TiNFs enzyme reactor is hydrophilic, and water droplets can be completely absorbed within 1 second ( Figure 2 f).

[0025] In a further design, the surface zeta potential of the prepared samples was studied. Figure 3 As shown in a, the C / TiNFs sample prepared from titanium dioxide nanofibers (TiNFs) and chitosan methacrylate (CSMA) has a positive potential of + 10.5 mV, and after modification with PGMA and PSBMA, the surface potential is reduced to about + 5.60 mV. In addition, the tannase-pGSC / TiNFs enzyme reactor has a negative potential of -5.31 mV, indicating that the tannase is successfully immobilized. Thanks to the excellent water wettability and high porosity (99.2%), the aqueous solution can flow quickly through the reactor under gravity without the need for additional auxiliary pressure.

[0026] Among them, the water flux of the biomimetic C / TiNFs, pGSC / TiNFs and tannase-pGSC / TiNFs enzyme reactors with a thickness of 15 mm was determined to be 2023, 2454 and 2432 Lm–2h–1, respectively ( Figure 3 b). High water flux and low physical flow resistance facilitate rapid reactant-product exchange in continuous flow catalytic reactions.

[0027] in addition, Figure 3 c shows the compressive stress-strain curves of the three samples, among which the compressive stress of the biomimetic tanninase-pGSC / TiNFs enzyme reactor (83.3 kPa) at 70% strain is higher than that of pGSC / TiNFs (60.4 kPa) and C / TiNFs (24.9 kPa). The compressive stress of the biomimetic tanninase-pGSC / TiNFs enzyme reactor at 70% stress is still higher than the compressive stress of biomimetic porous materials with similar structures reported in the literature.

[0028] Among them, the enzyme immobilization amount on the biomimetic reactor with PSBMA modification was determined, such as Figure 3 As shown in d, tannase-pGSC / TiNFs (98.4 mg g -1 ) was slightly lower than that of tannase-pGC / TiNFs (104.5 mg g -1 ).

[0029] The present invention studies the effects of tannase concentration, reaction time, pH value and temperature on the binding amount of fixed enzyme and enzyme activity. The results show that when the tannase dosage is 0.5 mg / mL -1 , pH value is 7.0, reaction temperature is 4 o C and a reaction time of 12 h, the best immobilization efficiency was achieved ( Figure 4 The data showed that the enzyme binding capacity, fixation efficiency and enzyme activity were 98.4 mg g and 1. -1 , 84.2% and 50.5Ug -1 .

[0030] In addition, the effects of pH, temperature, storage time, and number of cycles on the activities of Tannase-pGC / TiNFs, Tannase-pGSC / TiNFs, and free tannase were also studied. Figure 5As shown in a, the optimal pH value of free tannase is 7.0, while tannase-pGC / TiNFs and tannase-pGSC / TiNFs exhibited maximum activity at pH 6.5 and 6.0, respectively. In addition, in the pH range of 5.0 to 6.0, Tannase-pGC / TiNFs and Tannase-pGSC / TiNFs maintained 81.6–94.3% and 91.3–100% of their activities, respectively; in contrast, free tannase remained in a lower range of 56.7-81.2%. At pH 8.0, the retained activities of tannase-pGC / TiNFs (62.5%) and tannase-pGSC / TiNFs (81.2%) were both higher than that of free tannase (50.8%).

[0031] The results showed that the immobilized tannase had higher stability than the free tannase in a wider pH range, and this phenomenon was attributed to the modified polymers PGMA and PSBMA, which endowed Tannase-pGC / TiNFs and Tannase-pGSC / TiNFs with a buffering microenvironment and excellent protection, giving them a shielding effect.

[0032] Among them, the stability of immobilized tannase and free tannase at different temperatures was also studied, e.g. Figure 5 As shown in b, free tannase at 45 o C, while tannase-pGC / TiNF and tannase-pGSC / TiNF showed the maximum activity at 50 o C to achieve the best activity. In addition, the temperature from 45 o C rises to 65 o C caused the activities of Tannase-pGC / TiNFs and free tannase to decrease sharply to 71.2% and 48.1%, respectively, while Tannase-pGSC / TiNFs maintained a relatively high activity of 80.6% even at 70 o C, the residual activity of Tannase-pGSC / TiNFs was still better than that of Tannase-pGC / TiNFs and free tannase. These results were due to the covalent bonds between tannase and the solid supports in pGC / TiNFs and pGSC / TiNFs, which improved the molecular rigidity and thermal stability of the enzyme protein.

[0033] The storage stability of free and immobilized tannases was determined by incubating free tannase in a buffer solution at pH 7.0 and immobilized enzymes in a buffer solution at pH 6.5 for 63 days. Free tannase retained 17.8% of its initial activity, while tannase-pGC / TiNFs and tannase-pGSC / TiNFs retained 64.6% and 70.5% of their enzyme activities, respectively ( Figure 5c). In addition, after 10 consecutive cycles, Tannase-pGC / TiNFs and Tannase-pGSC / TiNFs showed high activity retention rates of 96.3% and 96.5%, respectively, but the relative activity of free tannase was 66.5% ( Figure 5 d) These results indicate that the protein structure of tannase is stable after covalent immobilization on the designed carrier.

[0034] Among them, the continuous flow catalytic conversion of tannins to gallic acid and glucose was also evaluated, e.g. Figure 6 As shown in a, the biomimetic tannase-pGSC / TiNFs enzyme reactor is fixed in the device, and the aqueous solution containing the reactants is pumped to the top surface of the biomimetic tannase-pGSC / TiNFs enzyme reactor. The aqueous solution flows through the Tannase-pGSC / TiNFs enzyme reactor to complete the catalytic reaction. The effect of flow rate on the conversion efficiency is also studied, as shown in Figure 6 As shown in b, when the flow rate is lower than 1.0 mg / mL –1 When the flow rate is increased, the conversion efficiency exceeds 99.6%. When the flow rate is further increased, the efficiency will gradually decrease. Too high a flow rate may lead to insufficient contact between the immobilized tannase and the reactants. The recyclability and long-term stability of the biomimetic tannase-pGSC / TiNFs enzyme reactor were studied. In the presence of the biomimetic tannase-pGSC / TiNFs enzyme reactor, the flow catalytic conversion of tannin was repeated for 10 cycles, and the conversion efficiency decreased slightly with the increase of the number of cycles ( Figure 6 c), the biomimetic tannase-pGSC / TiNFs enzyme reactor can still maintain 98.1% efficiency after 10 cycles, showing good recyclability. In addition, the biomimetic tannase-pGSC / TiNFs enzyme reactor can be operated continuously for 15 days, and the conversion efficiency can still be maintained at 82.4% efficiency ( Figure 6 d), therefore, the prepared biomimetic tannase-pGSC / TiNFs enzyme reactor has high conversion efficiency, good recyclability and long-term stability in the continuous bioconversion of tannins.

[0035] In summary, the biomimetic tannase-pGSC / TiNFs enzyme reactor of the present invention is composed of TiNFs, CSMA, PGMA, PSBMA and immobilized tannase, and has vertically arranged channels. Due to the characteristics of the reactor with honeycomb structure, rapid mass transfer, comfortable microenvironment and PSBMA-modified substrate enrichment effect, compared with the enzyme reactor without PSBMA and free tannase, the biomimetic tannase-pGSC / TiNFs enzyme reactor exhibits enhanced pH and thermal tolerance, thermal stability, storage stability and reusability. The modified PSBMA provides a buffering microenvironment and excellent protection, which helps to achieve high enzyme catalytic stability. Importantly, the biomimetic tannase-pGSC / TiNFs enzyme reactor can act as a tissue cell reactor, continuously and effectively converting tannins into gallic acid and glucose under continuous flow conditions, demonstrating the application potential of biomass conversion.

[0036] While the embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a bionic enzyme aerogel reactor, characterized in that: The specific steps include: Step S1, first preparing titanium dioxide nanofibers (TiNFs) by solvent thermal treatment; Step S2, freeze-casting and vacuum drying an aqueous dispersion containing titanium dioxide nanofibers (TiNFs), chitosan methacrylate (CSMA) and a cross-linking agent to obtain a biomimetic C / TiNFs aerogel reactor with vertically arranged channels; Step S3, polymerizing and modifying glycidyl methacrylate (GMA) monomer, methacryloylethyl sulfobetaine (SBMA) monomer and N,N'-methylenebisacrylamide (MBA) crosslinker on the skeleton of the biomimetic aerogel reactor; Step S4, covalently immobilizing tannase in a biomimetic aerogel reactor under mild conditions, thereby obtaining a biomimetic tannase-pGSC / TiNFs enzyme reactor.

2. The method for preparing a biomimetic enzyme aerogel reactor according to claim 1, characterized in that: The biomimetic tannase-pGSC / TiNFs enzyme reactor prepared in step S4 is cylindrical.

3. The method for preparing a biomimetic enzyme aerogel reactor according to claim 1, characterized in that: The biomimetic tannase-pGSC / TiNFs enzyme reactor prepared in step S4 exhibits a 3D hierarchical cell-like structure with honeycomb pores in the structure.

4. The method for preparing a biomimetic enzyme aerogel reactor according to claim 3, characterized in that: The size of the honeycomb holes is 20-100 μm, and the mesh hole walls are composed of nanofibers and polymers, with a thickness of 0.2-2 μm.

5. The method for preparing a biomimetic enzyme aerogel reactor according to claim 1, characterized in that: The biomimetic tannase-pGSC / TiNFs enzyme reactor also exhibits unidirectional, vertically arranged and interconnected channels in the longitudinal direction.

6. An application of a biomimetic enzyme aerogel reactor as claimed in any one of claims 1 to 5, characterized in that: The bionic tannase-pGSC / TiNFs enzyme reactor is applied in biocatalysis engineering.

Citation Information

Patent Citations

  • Mercapto-modified titanium dioxide nanofiber immobilized enzyme, preparation method thereof, and application of immobilized enzyme to 1,3-propylene glycol synthesis

    CN103602655A

  • Zwitter-ion magnetic composite hydrogel immobilized enzyme supporter and preparation method

    CN107746841A

  • Biological enzyme grafted with polymer and preparation method and immobilization method of biological enzyme

    CN110373405A

  • Co-crosslinking immobilization method of tannase

    CN110777129A

  • Preparation method of magnetic graphene oxide / multilayer nanocomposite immobilized tannase

    CN114214311A

Cited By

  • Aerogel collagen cell material as well as preparation method and application thereof

    CN122081302A